Chaucer's dead body : from corpse to corpus - Prendergast, Thomas A. (Thomas Augustine) (Routledge, 2004)
In Chaucer's Dead Body, Thomas Prendergast looks at the material reasons behind Chaucer's transformation into a touchstone for the whole of the Anglophone Middle Ages.